1970
DOI: 10.1139/v70-045
|View full text |Cite
|
Sign up to set email alerts
|

Dipole moments, charge-transfer parameters, and ionization potentials of the methyl-substituted benzene–tetracyanoethylene complexes

Abstract: The dipole moments of a series of charge-transfer complexes of methylbenzenes with tetracyanoethylene in carbon tetrachloride solutions at 25 "C and the various parameters derived from Mulliken's theory have been evaluated. The energies of various states of the complexes were calculated via their relationships with the parameters, charge-transfer transition energies, and heats of formation of the complexes by means of the variation principle. Vertical ionization potentials of the donors were obtained from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

1973
1973
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…In addition, the authors showed a linear correlation between the ionization potential of the donor species and the electronic transition energies of the charge transfer complexes investigated. 31 In fact, in Figure 2a, it can be observed a linear correlation between the transition energies (in cm -1 ) and the experimental ionization potentials, 32 where the relation is hν (cm -1 ) = 0.45IP -11105 (R 2 = 0.9993). Figure 2b shows the comparison of the experimental values observed for the charge transfer transition bands and the respective calculated values obtained by TDDFT.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…In addition, the authors showed a linear correlation between the ionization potential of the donor species and the electronic transition energies of the charge transfer complexes investigated. 31 In fact, in Figure 2a, it can be observed a linear correlation between the transition energies (in cm -1 ) and the experimental ionization potentials, 32 where the relation is hν (cm -1 ) = 0.45IP -11105 (R 2 = 0.9993). Figure 2b shows the comparison of the experimental values observed for the charge transfer transition bands and the respective calculated values obtained by TDDFT.…”
Section: Resultsmentioning
confidence: 91%
“…The trend observed for the transition energies of the complexes formed between TCNE and substituted anilines is very similar to the well behaved trend observed for the complexes of TCNE with methyl substituted benzenes and TCNE. Chan and Liao 31 showed in a systematic study for 13 substituted benzenes with increasing number of methyl groups, that the maximum absorption values range from 385 nm for TCNE-benzene complex to 535 nm for TCNE-hexamethylbenzene in CCl 4 solution. In addition, the authors showed a linear correlation between the ionization potential of the donor species and the electronic transition energies of the charge transfer complexes investigated.…”
Section: Resultsmentioning
confidence: 99%
“…[93,94] In other words, smaller IP (larger EA) values state easier injection of holes into the emissive layers from the hole (electron) transport layer. In general, the lower IP and higher EA mean better hole and electron transport.…”
Section: Ionization Potentials and Electron Affinitiesmentioning
confidence: 99%
“…In general, the lower IP and higher EA mean better hole and electron transport. [93,94] In other words, smaller IP (larger EA) values state easier injection of holes into the emissive layers from the hole (electron) transport layer. [48] All adiabatic ionization potential (IPa), vertical ionization potential (IPv), adiabatic electron affinity (EAa), and vertical electron affinity (EAv) of porphyrin and metallated porphyrins are computed and presented in Table 2.…”
Section: Ionization Potentials and Electron Affinitiesmentioning
confidence: 99%
“…The ionization potential and electron affinity are distinct properties that can be calculated by DFT to estimate the energy barrier for the injection of holes and electrons. The lower ionization potential revealed that material would be better as hole transporter [47] while higher electron affinity leads to be a better electron transport. We have tabulated the adiabatic ionization potential (IPa), vertical ionization potential (IPv), adiabatic electron affinity (EAa), and vertical .81 eV, respectively revealing decreased electron injection barrier compared to the parent molecule.…”
Section: Ionization Potential and Electron Affinitymentioning
confidence: 99%